1971
DOI: 10.1073/pnas.68.8.1757
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical In Vivo Transcription of Mitochondrial DNA in HeLa Cells

Abstract: RNA DNA hybridization experiments utilizing separated strands of HeLa mitochondrial DNA and mit-RNA from HeLa cells exposed to short pulses of have shown that the labeled RNA hybridizes with both the light (L) and the heavy (H) strand, though to a different relative extent depending upon the labeling time. Thus, hybridization of pulse-labeled RNA is about equal with the two strands when the pulse is very short (1-5 min), and becomes more and more predominant with the H strand with increasing pulse length. Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(88 citation statements)
references
References 14 publications
5
83
0
Order By: Relevance
“…It should be noted that the mtDNA light-strand transcripts, which contain the sequences of eight tRNAs, are synthesized at a rate at least 10 to 15 times higher than required to account for the steadystate levels of these tRNAs (7). Furthermore, it is known that these transcripts have a much shorter half-life than the heavystrand transcripts and do not accumulate to any significant extent (2,10). It is therefore a plausible hypothesis that the vast majority of these transcripts decay before the occurrence of any processing, which would lead to a maturation and stabilization of the tRNAs (7).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the mtDNA light-strand transcripts, which contain the sequences of eight tRNAs, are synthesized at a rate at least 10 to 15 times higher than required to account for the steadystate levels of these tRNAs (7). Furthermore, it is known that these transcripts have a much shorter half-life than the heavystrand transcripts and do not accumulate to any significant extent (2,10). It is therefore a plausible hypothesis that the vast majority of these transcripts decay before the occurrence of any processing, which would lead to a maturation and stabilization of the tRNAs (7).…”
Section: Discussionmentioning
confidence: 99%
“…Aloni and coworkers have reported that mitochrondrial DNA and DNA from papovaviruses are transcribed in a manner which leads to synthesis of complementary RNA sequences (19)(20)(21)(22). From studies on transcription of SV40 DNA Aloni (20) has proposed a model which postulates that both strands of SV40 DNA are completely transcribed.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial genes for proteins and tRNAs are located on both the heavy and light strands of the genome, which are transcribed as large polycistronic transcripts covering almost the entire length of each strand (Aloni and Attardi 1971;Murphy et al 1975;Montoya et al 1981;Mercer et al 2011). A third transcript covering the start of the heavy strand and the two rRNA genes is also produced (Christianson and Clayton 1988).…”
Section: Introductionmentioning
confidence: 99%